As múltiplas faces da comissão de frente no contexto da ópera de rua (1928-1999) - Corrêa, Elizeu de Miranda (2011)
In a real universe emerges from the current committees lies in front of Samba Schools of Rio de Janeiro. Conducting a historiographical route from 1928 to 1999. This study aims at discussing the concept, function and origin of this art form, and submit the changes and tensions that have occurred over its development process. In this sense, it is assumed that there were three major phases in chronological route, which defined the structure of the current model in front of committees. During these steps, it was noted that the voltage power and art, tradition and modernity, and technology were crucial factors to ruptures and continuities of these groups who parade in front of Samba Schools, heirs of large corporations, who paraded the clubs Carnival, which had emerged from the second half of the nineteenth century. Understanding the dynamics of the source and format of the Institution School of Samba, the processes of preparing a parade, as well as the questions of the show trial was necessary, that he might perceive the particularity of the question regarding the Front. Therefore, it is treated the context of these changes throughout this work presents the following questions: why change, how, where and what changes occurred. Issues that will understand how the power of technology, made the front commission of the samba school to become a show piece of the party, whose current role is to act as a prelude to the great street opera. The methodological development of this research was conducted through interviews and footage and photos of the parade of Samba Schools, regulations and worksheet scores of parades, and journals of the period studied